P715 Achievement and maintenance of endoscopic, histologic, and combined outcomes after extended induction in Week 10 nonresponders of ozanimod: 2-year interim analysis of the True North open-label extension study. (30th January 2023) - Vermeire, S; Colombel, J F; Rubin, D T; Ghosh, S; Jain, A; Lawlor, G; Osterman, M T; Wu, H; Canavan, J B; Chiorean, M V
Abstract: Background: Ozanimod, a novel oral therapeutic option for patients with moderately to severely active ulcerative colitis, demonstrated significant improvements in clinical, endoscopic, and histologic endpoints in the phase 3, 52-week, double-blind True North (TN) study. Approximately one-third of the patients did not achieve clinical response to ozanimod after 10 weeks of TN induction therapy. However, a delayed response was observed in a subset of these nonresponders upon extended induction with ozanimod. The present analysis evaluated ozanimod efficacy on endoscopic and histologic endpoints in these delayed responders in the TN open-label extension (OLE) study. Methods: Data were analysed for the overall delayed responder population and separately for the blinded (Cohort 1) and open-label (Cohort 2) cohorts (data cutoff: 10 January 2022, the point at which patient disposition was available for all patients up to OLE Week 94). Endpoints included endoscopic improvement (defined as an endoscopy subscore of ≤1 point), histologic remission (defined as Geboes index score <2.0), and mucosal healing (defined as endoscopy subscore of ≤1 point and Geboes index score of <2.0) up to OLE Week 94. The endpoints were evaluated using observed case (OC) and nonresponder imputation (NRI) analyses. Results: A total of 226 patients (Cohort 1, n=150; Cohort 2, n=76) were nonresponders at Week 10 and entered the OLE (67% male; mean [standard deviation] age, 39.6 [13.6] years). At OLE entry, 24% of patients had moderate disease (Mayo endoscopic score [MES]=2) and 73% had severe disease (MES=3). Approximately half of these patients achieved symptomatic clinical response as early as 5 weeks of ozanimod open-label treatment. In OC analysis at OLE Week 46, 30% of patients achieved endoscopic improvement, 42% achieved histologic remission, and 24% achieved mucosal healing that further increased to 48%, 48%, and 39%, respectively, by OLE Week 94 (Figure 1A). In NRI analysis, the following patient proportions were observed at OLE Weeks 46 and 94: 18% and 19% (endoscopic improvement), 22% and 14% (histologic remission), and 13% and 11% (mucosal healing) (Figure 1B). Data were generally similar in Cohorts 1 and 2. Conclusion: Delayed responders to ozanimod achieved and maintained mucosal healing over 2 years of continuous ozanimod treatment. Ozanimod treatment resulted in the healing of intestinal mucosal lesions, even in patients with moderate to severe disease who may have an initial delayed response to ozanimod.